Role of Information, Education, Communication and Training in Disaster Management - Dr. Vinod Kumar (Journal of Advanced Research in Education, 2024)
Information, Education and Communication (IEC) are of vital significance for disaster preparedness, prevention and mitigation. It promotes an alert community which is sine -qua non for any successful activity. IEC are the essential constituents of any programme especially in a disaster related scenario. IEC requires the administrative machinery, Non Governmental Organizations (NGOs), Community-based Organizations (CBOs), other agencies and the community to be prompt, active and well informed to carry out the activities confidently. Hence IEC should be given top priority in any disaster management programme. Creation of awareness is an integral part of the process of social development, communication has the power to liberate the minds and potential of people. Critical awareness is needed in every field linked to human development. The generation of an alert public will hinge on effective communication of information and ideas that relate to people’s needs, aspirations and capacities. In this sense, getting the: development process initiated is largely the task of information, education and communication. This research paper attempt to study the nature and significance of IEC and training, and the concept of community awareness. The important components and strategies of IEC and training shall also be focused.